2021
DOI: 10.1093/europace/euab175
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of controlled studies on minimally interrupted vs. continuous use of non-vitamin K antagonist oral anticoagulants in catheter ablation for atrial fibrillation

Abstract: Aims At present, there are no guideline recommendations for minimally interrupted use of non-vitamin K antagonist oral anticoagulants (mi-NOAC) during catheter ablation (CA) for atrial fibrillation (AF). Current evidence is predominantly based on observational studies, with continuous use of vitamin K antagonist in the control arm. This quantitative summary reflects the first high-level evidence on contemporary regimens, with continuous NOAC use (c-NOAC) as the current gold standard. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
1
17
0
7
Order By: Relevance
“…24 This risk reduction may be especially true for patients with a low CHA 2 DS 2 -VASc score, and access to continuous monitoring. 25,26 Accordingly, our respondents showed a tendency to terminate OAC in patients with paroxysmal AF and a low CHA 2 DS 2 -VASc score.…”
Section: Anticoagulation and Left Atrial Appendage Closure Devicementioning
confidence: 76%
“…24 This risk reduction may be especially true for patients with a low CHA 2 DS 2 -VASc score, and access to continuous monitoring. 25,26 Accordingly, our respondents showed a tendency to terminate OAC in patients with paroxysmal AF and a low CHA 2 DS 2 -VASc score.…”
Section: Anticoagulation and Left Atrial Appendage Closure Devicementioning
confidence: 76%
“…The possibility of overestimation cannot be excluded because of the asymptomatic embolic events that showed a high incidence after AF ablation in previous study ( 42 ). Recent meta-analysis reported that the incidence of silent cerebral embolism after AF ablation ranged from 10 to 24%, respectively ( 43 ). These are considered potential reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly in patients on DOAC therapy, only 24.6% of the physicians would routinely perform AF ablation without interruption of DOAC therapy, despite recent studies and guidelines advocating AF ablation without interruption of DOAC therapy as a Class I recommendation. 4 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…This change in clinical practice is probably supported by data demonstrating the safety of performing AF ablation without interruption of DOAC therapy and a potentially increased bleeding rate in patients who undergo heparin bridging. 3 , 26 The practice of performing AF ablation on uninterrupted anticoagulation therapy is also stated in recent guidelines and recommendations. 1 , 2 , 4 …”
Section: Discussionmentioning
confidence: 99%